IMPLEMENTASI MODEL PROBLEM BASED LEARNING TERINTEGRASI PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN CRITICAL THINKING SKILL PESERTA DIDIK SEKOLAH DASAR - Umi Melinda, Resti; Rohman, Fatkhur; Amrina Izzatika; Nelly Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research problem in this study is the low critical thinking skills of fourth-grade students due to the lack of varied teaching models used by educators. This study aims to describe and analyze the effect of the Problem-Based Learning model integrated with differentiated instruction on critical thinking skills in IPAS learning. This research employs a quasi-experimental design with a non-equivalent control group design. The population consists of all fourth-grade students at SD Negeri 1 Triharjo, totaling 54 students. The sample was determined using purposive sampling, a technique where the sample is selected from the population based on specific considerations. Data collection techniques include tests, observation sheets, and documentation. Hypothesis testing was conducted using simple linear regression, yielding F_calculated ≥ F_table (54.17 ≥ 4.26), leading to the conclusion that the Problem-Based Learning model integrated with differentiated instruction significantly affects the critical thinking skills of fourth-grade students in IPAS learning at SD Negeri 1 Triharjo.